"Nonsense Madrigals" by György Ligeti: The Musical Sense of Nonsense between Chaos and Order - Prusak, Monika (Res Facta Nova, 2021)
The study examines Ligeti’s “stylistic revolution” as well as the nonsense aspects of the composition and introduces an original analysis of Ligeti’s musical nonsense inspired by the literary analysis of nonsense by Susan Stewart. The Nonsense Madrigals by György Ligeti take part in a kind of “stylistic revolution” in Ligeti’s style and are the result of his passionate research on African polyrhythms and its contribution to his music. What Ligeti intended to create in those periods was a superimposition of different rhythmic and melodic patterns in such a way that they could fuse together in an illusory chaos. However, there is also an ancient order that governs this new approach: the old masters such as Philippe de Vitry, Johannes Okeghem or Johannes Ciconia and their compositional techniques became the base of mixing the old western styles with the traditional music of Central Africa, so that the new and authentic compositional idea could blossom. The copious sketches of the Nonsense Madrigals, stored at the Paul Sacher Stiftung in Basel, reveal that the preparatory brainstorming involved also many other inspirations such as Balkan and oriental music, jazz, and some of Ligeti’s own compositions. The combination of the old and the new without using concrete models but just drawing inspiration marks a new approach among Ligeti’s contemporaries.